1999
DOI: 10.1046/j.1365-8711.1999.02373.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical and ultraviolet observations of a strong flare in the young, single K2 dwarf LQ Hya

Abstract: A B S T R A C TWe present high-resolution optical echelle spectra and IUE observations during a strong¯are on 1993 December 22 in the very active, young, rapidly rotating, single K2 dwarf LQ Hya. The initial impulsive phase of the¯are, which started sometime between 2:42 ut and 4:07 ut, was characterized by strong optical continuum enhancement and blueshifted emission lines with broad wings. The optical chromospheric lines reached their maximum intensity at <5:31 ut, by which time the blueshift vanished and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 48 publications
9
50
0
Order By: Relevance
“…For the He i lines at 3819.6, 4026.2, and 6678.1 Å the line amplitudes are not strong enough to reveal a broad component, although the latter at least shows a second component. These broad component has been noted mostly in M-dwarf flares (Crespo-Chacón et al 2006;Fuhrmeister et al 2008Fuhrmeister et al , 2011, but also for young K-dwarfs (Montes et al 1999 and references therein). They can be blue-or (more often) red-shifted, and are often ascribed to a moving turbulent plasma component.…”
Section: Broad Line Componentsmentioning
confidence: 85%
See 1 more Smart Citation
“…For the He i lines at 3819.6, 4026.2, and 6678.1 Å the line amplitudes are not strong enough to reveal a broad component, although the latter at least shows a second component. These broad component has been noted mostly in M-dwarf flares (Crespo-Chacón et al 2006;Fuhrmeister et al 2008Fuhrmeister et al , 2011, but also for young K-dwarfs (Montes et al 1999 and references therein). They can be blue-or (more often) red-shifted, and are often ascribed to a moving turbulent plasma component.…”
Section: Broad Line Componentsmentioning
confidence: 85%
“…Also Kowalski et al (2010) observed a white light mega-flare on YZ CMi with a resolving power below 1000 but a cadence of 30 s covering a wavelength range from 3350 to 9260 Å. Prominent examples of good spectral resolution but lower cadence are Montes et al (1999), who observed a major flare on LQ Hya during decay and about half an hour before its onset with R ∼ 35 000 and a cadence of six to seven minutes in the wavelength range between 4842 to 7725 Å. Fuhrmeister et al (2008) observed CN Leo during a mega-flare with a cadence of about 15 min and R ∼ 50 000.…”
Section: Introductionmentioning
confidence: 99%
“…Ottmann and Schmitt, 1996;Tsuboi et al, 1998), perhaps due to the presence of cool material from erupting filaments. Blue-shifted Hα emission during flares, indicating velocities of order 100 km s −1 , also support the presence of CMEs (Montes et al, 1999;Fuhrmeister and Schmitt, 2004). Complex behavior of optical and ultraviolet lines during a large flare on the M dwarf AD Leo was interpreted in terms of various phases of a mass ejection including motion of filaments, chromospheric condensation, prominence oscillations, and the prominence eruption itself (Houdebine et al, 1993).…”
Section: Implications For Cmes From Other Starsmentioning
confidence: 91%
“…Similarly, Johns-Krull et al (1997) report on a GOES M7.7 class solar flare also finding the He i D3 line to be in absorption throughout the entire event and absent during quies-During flares on other stars the He i D3 line has been observed in emission. For instance, Crespo-Chacón et al (2006) detect the line studying flares on the active M-type star AD Leo and Montes et al (1999) report He i D3 emission during a flare on the K2 dwarf LQ Hya. Our observations indicate a potential small increase in the He i D3 flux during the rise phase of the flare, which would be consistent with observations of strong flares on the Sun, thereafter a phase of increasing absorption follows.…”
Section: The Behavior Of He I D3mentioning
confidence: 99%